The Influence of Emotional Intelligence, Self-Efficacy, and Gender on the Level of Academic Stress of Students Working on Thesis Tasks in the Business Education Study Program, Medan State University - Rianto Harapan Munthe (Outline Journal of Education, 2023)
The purpose of this study was to determine the effect of emotional intelligence, self-efficacy, and gender partially and simultaneously on the level of academic stress of students working on their thesis assignments in business education study program, at Medan State University. This study uses a quantitative approach. Data analysis technique using multiple linear regression test. Test the hypothesis using the t-test, f-test, and different tests using the Independent Samples t-test. The results of this study indicate that there is an influence of emotional intelligence on the academic stress level of 2018 Stambuk Business Education students UNIMED. There is an effect of self-efficacy on the academic stress level of 2018 Stambuk Business Education students UNIMED. There is a gender effect on the academic stress level of 2018 Stambuk Business Education students UNIMED There are differences in average stress levels between male students and female students. Where the stress level of male students has a higher average academic stress level when compared to female students in the 2018 Stambuk Business Education.